2002
DOI: 10.1146/annurev.biophys.31.082901.134439
|View full text |Cite
|
Sign up to set email alerts
|

The Search and Its Outcome: High-Resolution Structures of Ribosomal Particles from Mesophilic, Thermophilic, and Halophilic Bacteria at Various Functional States

Abstract: We determined the high-resolution structures of large and small ribosomal subunits from mesophilic and thermophilic bacteria and compared them with those of the thermophilic ribosome and the halophilic large subunit. We confirmed that the elements involved in intersubunit contacts and in substrate binding are inherently flexible and that a common ribosomal strategy is to utilize this conformational variability for optimizing its functional efficiency and minimizing nonproductive interactions. Under close-to-ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
69
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 74 publications
6
69
0
2
Order By: Relevance
“…A head-to-shoulder motion in the small subunit [Plate 1(a)] allows threading of the incoming mRNA through a dynamic pore, and the platform, located at the opposite side of the particle, is likely to perform the motions that facilitate the mRNA exit. 4,[19][20][21] The pivotal point for this motion is probably the connection between the head and the main structural junction, in the vicinity of the binding site of spectinomycin, an antibiotic found to trap the small subunit at a particular conformation, thus disabling the head motions. 22 During elongation, the mRNA advances along a curved channel on the small subunit interface, and in order to ensure cognate tRNA selection at the A-site [Plate 1(a)], a specific conformation of the small subunit is required.…”
Section: Spectacular Ribosomal Architecture Global Motionsmentioning
confidence: 99%
See 2 more Smart Citations
“…A head-to-shoulder motion in the small subunit [Plate 1(a)] allows threading of the incoming mRNA through a dynamic pore, and the platform, located at the opposite side of the particle, is likely to perform the motions that facilitate the mRNA exit. 4,[19][20][21] The pivotal point for this motion is probably the connection between the head and the main structural junction, in the vicinity of the binding site of spectinomycin, an antibiotic found to trap the small subunit at a particular conformation, thus disabling the head motions. 22 During elongation, the mRNA advances along a curved channel on the small subunit interface, and in order to ensure cognate tRNA selection at the A-site [Plate 1(a)], a specific conformation of the small subunit is required.…”
Section: Spectacular Ribosomal Architecture Global Motionsmentioning
confidence: 99%
“…22 Similarly, the two large subunit lateral protuberances, namely the L7/L12 stalk and the L1 arm [Plate 1(b)], were shown to possess dynamic properties and can undergo substantial conformational rearrangements. 21 By analyzing the available ribosomal high-resolution structures, a correlation between their structure and the functional state of the ribosome was revealed. Thus, they assume well defined, albeit dramatically different conformations in the complexed ribosome 6 compared with the unbound large ribosomal subunit, 7 They can readily become disordered [Plate 1(b)] when exposed to an environment which is very different from that leading to efficient protein biosynthesis, as seen in the crystal structure of the large subunit from Haloarcula marismortui, H50S.…”
Section: Spectacular Ribosomal Architecture Global Motionsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the publication of the X-ray structures of the prokaryotic and archaeal ribosome, there is an opportunity to look at noncrystallographic structural measurements to assess the agreement between different types of data. The hypothesis behind this work is that data that are incompatible with published crystal structures may provide coherent patterns that suggest alternative conformations complementary or additional to those observed by crystallography (Yusupov et al 2001;Brodersen et al 2002;Ramakrishnan 2002;Yonath 2002 and references therein), and other experimental methods (see Lodmell and Dahlberg 1997;Frank and Agrawal 2000). It has been suggested that biochemical proximity measurements, such as crosslink, footprint, and cleavage experiments, may contain clues to ribosomal structural fluctuations and dynamics ribosome (see Sommer and Brimacombe 2001).…”
Section: Introductionmentioning
confidence: 95%
“…Electron and x-ray diffraction are well established tools to investigate the structures of solid state samples [1], for example in transmission electron microscopy [2] or xray crystallography [3,4]. Furthermore, electron diffraction has found broad application for gas-phase structuredetermination in chemistry [5].…”
mentioning
confidence: 99%